Study on fabrication and effectiveness evaluation of modified graphene and metals nanoparticles lubricating additive system - Nguyễn Hữu Vân; Nguyễn Duy Anh (Journal of Military Science and Technology, 2022)
In this paper, we report the fabrication of an anti-wear, anti-friction lubricating additive system based on modified graphene and modified Ag nanoparticles. The addition of the lubricating additive system to engine oil does not change the characteristics of the oil, but increases lubricating efficiency due to reduced friction, and leads to an increase in engine power 5% and 12.2% with tested engine, reducing fuel consumption by 10%, reducing CxHy pollutant emissions by ≥30% and reducing smoke by 57% depending on the working mode of the engine. The effectiveness of the synthesis and modification process of graphene and Ag nanoparticles were analyzed by FTIR, TGA, SEM, and TEM. The lubricating properties of the additive system and oil were evaluated according to the ASTM D2783 standard. The effectiveness of engine power increase, fuel consumption, and emissions reduction was evaluated by Tested on 1.25-ton diesel transport vehicles and S195 single-cylinder diesel engine.